2020
DOI: 10.3390/atmos11040353
|View full text |Cite
|
Sign up to set email alerts
|

Late 21st Century Projected Changes in the Relationship between Precipitation, African Easterly Jet, and African Easterly Waves

Abstract: The present study utilizes three high-resolution simulations from the Regional Climate Model version 4 (RegCM4) to examine the late 21st century changes (2080–2099) in the West African Monsoon (WAM) features. A set of three Earth System Models are utilized to provide initial and lateral boundary conditions to the RegCM4 experiments. Our analysis focuses on seasonal mean changes in WAM large-scale dynamical features, along with their connections with the summer monsoon precipitation. In the historical period, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 72 publications
0
10
1
Order By: Relevance
“…The regional climate model version 4.5.0 (hereafter RegCM4; Giorgi et al 2012) was used in the present study. RegCM4 is a limited area model and has been used for numerous studies including process studies (Sylla et al 2015;Diallo et al 2016;Kébé et al 2020) and future climate projections (Diallo et al 2016;Sawadogo et al 2020;Ashfaq et al 2020;among others). Performance of the RegCM4 model has been examined in tropical Africa as in Ogwang et al (2016); Komkoua et al (2017) andN'Datchoh et al (2018).…”
Section: Model Descriptionmentioning
confidence: 99%
“…The regional climate model version 4.5.0 (hereafter RegCM4; Giorgi et al 2012) was used in the present study. RegCM4 is a limited area model and has been used for numerous studies including process studies (Sylla et al 2015;Diallo et al 2016;Kébé et al 2020) and future climate projections (Diallo et al 2016;Sawadogo et al 2020;Ashfaq et al 2020;among others). Performance of the RegCM4 model has been examined in tropical Africa as in Ogwang et al (2016); Komkoua et al (2017) andN'Datchoh et al (2018).…”
Section: Model Descriptionmentioning
confidence: 99%
“…It is unclear how the frequency of AEWs will change in future, with studies projecting both increasing (Bercos‐Hickey & Patricola, 2021; Hannah & Aiyyer, 2017; Skinner & Diffenbaugh, 2014) and decreasing (Kebe et al., 2020) AEW activity. This is further complicated by a projected multi‐model average increase and decrease of the northern and southern AEW tracks respectively, albeit with a large spread among individual climate models (Brannan & Martin, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A similar result was reported by Brannan and Martin (2019) in their study of AEW tracks. A contrasting result of reduction of AEW activity throughout the region was reported by Kebe et al (2020) in their study using Regional Climate Model 4 (RegCM4). Similarly Mariotti et al (2014) also reported a reduction in 6-9 day AEW activity by the end of the century.…”
Section: Introductionmentioning
confidence: 81%